FUNGITOXIC AND INSECT REPELLENT EFFICACY OF SOME SPICES - and S. C. TRIPATHI, S. DUBE, P. D. UPADHYAY (Indian Phytopathology, 2002)
Essential oils from seeds of Apium graveolens. Cuminum cyminum and Zanthoxylum alatum were fungistatic at lower doses but turned fungicidal at higher doses against aflotoxin producing stains of Aspergillus flavus (NRRL 3251) and A. parasiticus (NRRL 2999). The fungitoxic property of the oils was thermostable, durable and of broad spectrum. All the oils were repellent to the test insect, Allocophora foueicollis; the oil of Z. alatum being most efficacious.